ANALYSIS OF EARLY READING AND WRITING (MMP) SKILL FOR THE FIRSTGRADE STUDENTS AT SDN MLATEN 1 - Aqidatul Izza TPP; Erna Yayuk; Innany Mukhlishina (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Early Reading Writing Learning (MMP) is a learning activity for students in low grades in order to acquire initial reading and writing skills. Early Reading Writing Learning (MMP) is a teaching and learning activity that is intended to provide provision for first-grade students to have good reading and writing skills. Early Reading and Writing Learning (MMP) isessential for students in the lower grades to master it as a basis for further preparation at the next level. The research aims to analyze the Early Reading and Writing Skills for first-grade students at SDN Mlaten 1. The research is a qualitative research approach. The researchsubjects are a total of 29 first-grade students. The research was conducted in the even semester of the 2022/2023 academic year, starting from February 21 to March 1, 2023. The research used several data collection methods like observation, interviews, tests, and documentation. The earlyreading and writing skills of grade 1 students at SDN Mlaten 1 are moderate. Out of a total of 29 first-grade students at SDN Mlaten 1, 8 students had high MMP skills, 11 students had moderate skills, and 10 students had low MMP skills.